DNA damage and DNA damage response in chronic myeloid leukemia - Popp, Henning; Samra, Vanessa; Naumann, Nicole; Flach, Johanna; Brendel, Susanne; Kleiner, Helga; Weiß, Christel; Seifarth, Wolfgang; Saußele, Susanne; Hofmann, Wolf-Karsten; Fabarius, Alice (International journal of molecular sciences, 2020)
DNA damage and alterations in the DNA damage response (DDR) are critical sources of genetic instability that might be involved in BCR-ABL1 kinase-mediated blastic transformation of chronic myeloid leukemia (CML). Here, increased DNA damage is detected by γH2AX foci analysis in peripheral blood mononuclear cells (PBMCs) of de novo untreated chronic phase (CP)-CML patients (n = 5; 2.5 γH2AX foci per PBMC ± 0.5) and blast phase (BP)-CML patients (n = 3; 4.4 γH2AX foci per PBMC ± 0.7) as well as CP-CML patients with loss of major molecular response (MMR) (n = 5; 1.8 γH2AX foci per PBMC ± 0.4) when compared to DNA damage in PBMC of healthy donors (n = 8; 1.0 γH2AX foci per PBMC ± 0.1) and CP-CML patients in deep molecular response or MMR (n = 26; 1.0 γH2AX foci per PBMC ± 0.1). Progressive activation of erroneous non-homologous end joining (NHEJ) repair mechanisms during blastic transformation in CML is indicated by abundant co-localization of γH2AX/53BP1 foci, while a decline of the DDR is suggested by defective expression of (p-)ATM and (p-)CHK2. In summary, our data provide evidence for the accumulation of DNA damage in the course of CML and suggest ongoing DNA damage, erroneous NHEJ repair mechanisms, and alterations in the DDR as critical mediators of blastic transformation in CML.